Emotion Aware Teaching: Connecting Emotion Recognition for Engaging Language Learning - Kok Wah, Jack Ng (Journal of Qualitative Research in Education, 2025)
In recent years, teaching has shifted from focusing only on academic skills to also paying attention to students’ emotions. This approach, known as emotion-aware teaching, aims to improve students’ engagement, confidence, and communication by understanding and responding to their feelings in class. Although many studies have investigated this topic, there are still gaps. These include inconsistent ways of measuring emotions, mixed opinions on how technology affects student motivation, and limited comparisons across different classroom settings. This review examines how emotion recognition supports language learning and how other factors such as multimodal data, perception-based assessments, and personalised feedback can influence students’ engagement. The findings come from various experiments and studies that explore how students feel during lessons. A key contribution of this review is the idea of integrating emotion-aware frameworks into the classroom. This means connecting students’ thinking abilities with their emotional needs so they can become both academically strong and emotionally intelligent. The research uses methods such as experiments, surveys, language data analysis, and cross-case comparisons. The review shows that emotion-based teaching methods can boost student motivation, lower anxiety, and support independent learning. While the findings show clear improvements in student engagement and teacher adaptability, they are limited by short-term studies and new evaluation tools. Future research should look at long-term effects, cultural differences, and practical classroom challenges. In conclusion, emotion-aware teaching helps create a healthier and more supportive environment for language learning by valuing students as emotional individuals, not just learners.